2000
DOI: 10.1080/10635150050207447
|View full text |Cite
|
Sign up to set email alerts
|

War of the Iguanas: Conflicting Molecular and Morphological Phylogenies and Long-Branch Attraction in Iguanid Lizards

Abstract: Recent studies based on different types of data (i.e., morphology, molecules) have found strongly conflicting phylogenies for the genera of iguanid lizards but have been unable to explain the basis for this incongruence. We reanalyze published data from morphology and from the mitochondrial ND4, cytochrome b, 12S, and 16S genes to explore the sources of incongruence and resolve these conflicts. Much of the incongruence centers on the genus Cyclura, which is the sister taxon of Iguana, according to parsimony an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 78 publications
(88 reference statements)
4
93
1
1
Order By: Relevance
“…For MP and ML, nodal support was tested by bootstrapping (29), with 1,000 pseudoreplicates. A. cristatus, the sister taxon of Conolophus (30), was used as an outgroup within the Iguaninae group. Alternative tree topologies were investigated using the S-H test (31).…”
Section: Methodsmentioning
confidence: 99%
“…For MP and ML, nodal support was tested by bootstrapping (29), with 1,000 pseudoreplicates. A. cristatus, the sister taxon of Conolophus (30), was used as an outgroup within the Iguaninae group. Alternative tree topologies were investigated using the S-H test (31).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, common objections to the use of many morphological characters on the basis of their being highly polymorphic or continuous may not be warranted. For example, Wiens and Hollingsworth (2000) and Smith and Gutberlet (2001) have shown that even highly polymorphic characters can contribute positively to cladistic structure. Furthermore, although continuously variable characters are generally excluded (Pimentel and Riggins 1987;Cranston and Humphries 1988) or variously recoded as categorical in phylogenetic analyses (Archie 1985;Thiele 1993;Rae 1998), there is no compelling reason for their exclusion or their coding into discrete states (Farris 1970;Felsenstein 1988).…”
Section: On Resolving Species-level Phylogeniesmentioning
confidence: 99%
“…The large-scale tree topology follows Estes et al (1988), rather than the single-gene-based analysis of Harris et al (1999). Within Iguania, we followed the family-rich nomenclature of Frost and Etheridge (1989), although some relationships were clarified by Wiens and Hollingsworth (2000) [iguanids (e.g. Dipsosaurus) basal within Iguania], Schulte et al (1998; agamid placement within Iguania) and Macey et al (1997; crotaphytids sister to phrynosomatids).…”
Section: Phylogenymentioning
confidence: 99%